Perbincangan tentang Pendidikan Islam di Indonesia - Muhaimin, Muhaimin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
The Indonesian people and government, which had inherited the dualistic education system, both the colonial education and Islamic educational systems, did not give priority to one of them, but they endeavored to integrate it to be